The Iceland–Jan Mayen plume system and its impact on mantle dynamics in the North Atlantic region: Evidence from full-waveform inversion ... - Rickers, Florian; Fichtner, Andreas; Trampert, Jeannot (ETH Zurich, 2013)
We present a high-resolution S-velocity model of the North Atlantic region, revealing structural features in unprecedented detail down to a depth of 1300 km. The model is derived using full-waveform tomography. More specifically, we minimise the instantaneous phase misfit between synthetic and observed body- as well as surface-waveforms iteratively in a full three-dimensional, adjoint inversion. Highlights of the model in the upper mantle include a well-resolved Mid-Atlantic Ridge and two distinguishable strong low-velocity regions beneath Iceland and beneath the Kolbeinsey Ridge west of Jan Mayen. A sub-lithospheric low-velocity layer is imaged beneath much of the oceanic lithosphere, consistent with the long-wavelength bathymetric high of the North Atlantic. The low-velocity layer extends locally beneath the continental lithosphere of the southern Scandinavian Mountains, the Danish Basin, part of the British Isles and eastern Greenland. All these regions experienced post-rift uplift in Neogene times, for ... : Earth and Planetary Science Letters, 367 ...